Design and development of strategic disaster management database for lead responding agency in Malaysia during response and early recovery phases / Khairilmizal Samsudin … [et al.] - Samsudin, Khairilmizal; Hussin @ Mohamad, Mohamad Fahmi; Mohd Yassin, Ahmad Ihsan; Kamarudin, Ainul Husna; Jusoh, Mohamad Huzaimy; Sulaiman, Ahmad Asari; Saadun, Jamil; Kasri, Mohd Haikal; Hussain, Abdul Razak (Faculty of Electrical Engineering, Universiti Teknologi MARA, Shah Alam, 2017)
The MNSC 20 has been outlined as a policy in managing disaster in Malaysia specifically for response and recovery phase. The presence experts during disaster response and recovery will increase the effectiveness of the operations but experts may not always be available. Hence, responders, especially from lead responding agency, need a computerized system in assisting them to manage response and recovery operations, namely IDMS, which consist of a web-based system and a database. Studies have the objective to design and develop the IDMS-database through using document review, observations and survey questionnaire methods, these. Based on the elements of effective disaster management, observations and survey questionnaire were administered to lead responding agency officers. Results indicate that IDMS-database designed based on ERD have a total of 12 entities and 69 attributes. The IDMS-database ERD was validated by six (6) domain experts where each agrees of the entities and attributes outlined. At the same time, XAMPP was used in developing SQL database where entities and attributes are represented in form of tables and columns. The design and development of IDMS-database will ensure the smooth development of IDMS fulfilling the criteria of a computerized system for lead responding agency in Malaysia